2010
DOI: 10.1111/j.1600-0625.2010.01172.x
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 signalling is dispensable for protective immunity in Leishmania-resistant mice

Abstract: Leishmaniasis is a parasitic disease affecting 12 million people. Control of infection (e.g. in C57BL ⁄ 6 mice) results from IL-12-dependent production of IFNc by Th1 ⁄ Tc1 cells. In contrast, BALB ⁄ c mice succumb to infection because of preferential Th2-type cytokine induction. Infected dendritic cells (DC) represent important sources of IL-12. Genetically determined differences in DC IL-1a ⁄ b production contribute to disease outcome. Whereas the course of disease was not dramatically altered in IL-1RI ) ⁄ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 18 publications
4
26
0
2
Order By: Relevance
“…Interleukin-1//b C57BL/6 mice deficient for IL-1//b or IL-1RI (the receptor for IL-1/ and IL-1b) can perfectly control L. major infection, and in some cases even exhibit a less severe pathology and lower parasite burden than WT mice [35,36]. This suggests that IL-1/ or IL-b signaling is dispensable for the control of Leishmania parasites in resistant mice.…”
Section: Toll-like Receptor Agonistsmentioning
confidence: 87%
See 1 more Smart Citation
“…Interleukin-1//b C57BL/6 mice deficient for IL-1//b or IL-1RI (the receptor for IL-1/ and IL-1b) can perfectly control L. major infection, and in some cases even exhibit a less severe pathology and lower parasite burden than WT mice [35,36]. This suggests that IL-1/ or IL-b signaling is dispensable for the control of Leishmania parasites in resistant mice.…”
Section: Toll-like Receptor Agonistsmentioning
confidence: 87%
“…However, the defect in iNOS induction observed in this case may result from a defect in IFNg production. In fact, since IL-1 signaling deeply alters T cell development and effector functions during L. major infection [36], it is particularly difficult to isolate the respective role of these cytokines from that of IFNg. A recent study highlighted the close interaction between IL-1 and IFNg signaling during L. major infection by demonstrating that in this context, skin commensals promote IFNg secretion by effector T cells through IL-1 signaling [39].…”
Section: Toll-like Receptor Agonistsmentioning
confidence: 99%
“…65 In an experimental study realized in mice, Leishmania major-infected IL-1α/β(-/-) mice were resistant to experimental CL compared to controls. 66 A recent trial carried by Haruko Ota et al showed that pretreatment of macrophages with the combination of IFN-γ and IL-12 induces resistance to L. major at the early phase of the infection. 67 Immune prophylaxis…”
Section: Cytokinesmentioning
confidence: 98%
“…Whereas it contributed to NO-mediated resistance to L. amazonensis, L. braziliensis and L. infantum-chagasi [45], IL-1 production was irrelevant [46] or detrimental in early L. major infections and the effect should be mediated by Th2-bias adaptive immune response [47]. IL-1b was one of the genes significantly stronger up-regulated in resistant C57BL/6 mice vs susceptible BALB/c mice although the analysis was made from 16 h L. major infected mice [48].…”
Section: Discussionmentioning
confidence: 99%